MODEL RAPID APPLICATION DEVELOPMENT UNTUK RANCANG BANGUN SISTEM INFORMASI TEMPAT PEMAKAMAN UMUM - Frieyadie Frieyadie (JITK (Jurnal Ilmu Pengetahuan dan Teknologi Komputer), 2017)
The availability of land for burial in Jakarta increasingly critical. DKI Jakarta with an area of approximately 65 thousand hectares, currently only has 589.7 hectares of a cemetery that has been used up to 80%. Each month, approximately 2 hectares of unused land burial because the death rate reached 110 people per day. According to Currently, there are 76 burial sites in Jakarta. Based on the results of a survey conducted at several locations Taman Pemakaman Umum (TPU) in Jakarta, does not have an information system that is used to record, how many people who died were buried in the gravesite TPU, it would be difficult for the officer must inspect or search for one by one file in the office of TPU. Heir or people do not know whether relatives are buried there or not, or the bodies buried ditumpang with new jenajah. Judging from the above problems, needed an information system that can be easily accessed by the public, the most convenient solution created a web-based information system for the public and officers, in view of data from anywhere. Model development is a model system used by Rapid Application Development (RAD).